Appendiceal bleeding in an elderly male: a case report and a review of the literature - Yuto Maeda; Seiya Saito; Mayuko Ohuchi; Yuka Tamaoki; Jiro Nasu; Hideo Baba (Surgical Case Reports, 2021)
Abstract Background The prevalence of acute lower gastrointestinal bleeding has been increased including colonic diverticulitis and angioplasty. However, appendiceal bleeding is extremely rare. Case presentation We present a case of lower gastrointestinal bleeding from the appendix in an elderly male who presented with melena. Appendiceal bleeding was diagnosed using lower gastrointestinal endoscopy, and laparoscopic appendectomy was performed. The patient did not have melena postoperatively, and was discharged 6 days after the surgery. Conclusion It is important to distinguish appendiceal bleeding from lower gastrointestinal bleeding and to treat it as soon as possible with less invasiveness.